Peran Telemedisin sebagai Sarana Menurunkan Angka Obsessive-Compulsive Disorder di Masa Pandemi COVID-19 Varian Omicron di Indonesia - Samosir, Fauzan Azmi Hasti Habibi; Panjaitan, Jeremia Aris Pandapotan; Kathy (Talenta Publisher, 2025)
Background: The COVID-19 pandemic, especially in the Omicron variant era, has brought major changes to the daily lives of the global community, including policies such as work-from-home (WFH) and limiting social access, and straightforward health services. The combination of prolonged social distancing and chronic psychological stress contributes to the increasing prevalence and worsening of obsessive-compulsive disorder (OCD). Objectives: This research explores the potential role of telemedicine as an interprofessional collaboration platform to support the diagnosis and management of OCD during the Omicron COVID-19 wave in Indonesia. Methods: This research uses a literature review method with the keywords